47 Demonstrating safe prescribing at the end of life after the gosport war memorial hospital report: a regional survey of inpatient hospice practice. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Thorns, Andrew; Ward, David; Parker, Georgina; Butler, Claire; Hajallie, Habiba; Kennedy, Ben; McGee, Helen
Abstract : Background: The Gosport War Memorial Hospital (GWMH) report highlighted significant concerns relating to opioid and sedative prescribing at the end of life. It concluded that the lives of over 450 people were shortened and probably at least another 200 patients were similarly affected. In light of the concern this might raise for the public, the seven hospices in Kent and Medway undertook to compare practice in end of life prescribing and communication. Methods: A medication and record review of patients dying in the in patient units who were admitted for >24 hours. To identify patterns of opioid and sedative prescribing and outlying cases for peer review. Results: Continuous subcutaneous infusions (syringe drivers) were used in 70%–95% of patients. Specific explanation to patient or families for their use varied greatly from 20%–100%. This may in part be due to different interpretation of the standard. Discussion with family that the patient was dying was recorded in 63%–100% of cases. Mean parenteral morphine dose/24 hours varied from 44–141 mg with corresponding medians: 30–60 mg. The highest dose used was 930 mg. Mean midazolam doses ranged from 15–34 mg. Median 10–17 mg with the highest dose in 24 hours being 130 mg Levomepromazine was used in less than a third of cases and haloperidol in approximately 10%. Phenobarbitone was used once at the final 24 hour dose was 1200 mg Conclusion: Whilst our doses are generally comparable with previously published studies, comparing opioid and sedative doses across units enables peer review of the exceptional cases. Improved communication with patients and relatives about CSCI use and approaching death are needed in some of the units. This survey tool and process offer patients, families and hospice governance structures reassurance that the shocking findings from GWMH are not a risk in these units.